Jual Beli di Bawah Tangan yang dilakukan oleh Kepala Adat Atas Tanah Petuanan - Saputan, Robert Lowell; Pide, A. Suryaman Mustari; Nur, Sri Susyanti (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to determine legal certainty and protection against buying and selling that is not under state regulations carried out by Customary Heads on customary land. This research was conducted using empirical legal research methods with a statute approach and a conceptual approach. They are collecting data in this study using field research techniques and literature research techniques. The data obtained, both primary and secondary data, were analyzed qualitatively. The results showed that customary land could only be managed, owned, and in principle can be handed over or sold to fellow indigenous and tribal peoples’. As for buying and selling of customary land, it must be proven by a letter of relinquishment of rights and a certificate issued by the Customary Head. In addition, for those who are not indigenous and tribal peoples’, if the material requirements of the legal relationship of buying and selling of land have been fulfilled, the buying and selling of customary land carried out by the Customary Head as based on customary law procedures is considered valid. This letter is the proof of ownership recognized by indigenous and tribal peoples’ in Ambon City, even though the letter is an inauthentic deed. On the other hand, a letter of relinquishment of rights and a certificate issued by the Customary Head are among the documents required by the Ambon City National Land Agency to register land title certificates. Therefore, the National Land Agency needs to raise legal awareness for customary land buyers. As for the party who buys customary land, it is necessary to follow up at the Land Office to immediately register the title of title to land to reduce the risk of overlapping ownership and even disputes over customary land.